Pathways to Healing: Forgiveness and Spiritual Growth for Domestic Violence Survivors in Islam - Salama, Nadiatus (The Faculty of Islamic Theology and Humanities, UIN Walisongo Semarang, Indonesia, 2024)
Forgiveness plays a crucial role in the psychological recovery of domestic violence (DV) survivors, and within the framework of Islamic teachings, it is seen as a means of attaining inner peace and spiritual healing. This study explores the role of forgiveness in the psychological and spiritual healing of domestic violence (DV) survivors within an Islamic framework. Employing a qualitative case study approach through in-depth interviews, semi-structured interviews, and observations with a single female DV survivor in Solo, Indonesia, to gain insights into the complex, non-linear journey of forgiveness. This study investigates the forgiveness process that aligns with Islamic principles of mercy (rahmah), patience (sabr), and divine justice. The findings reveal that the process of forgiveness is complex, non-linear, and influenced by various dynamics, including feedback and feed-forward loops, with survivors revisiting earlier stages. This process is often unpredictable, with survivors revisiting previous stages they thought were overcome, accompanied by changes in attitude. Victims' motivation to forgive is frequently influenced by a desire to accept the situation sincerely, often aligned with religious teachings. Additionally, releasing negative emotions is a significant driving force in the forgiveness process. Social support from family, community, and religious institutions is crucial in encouraging victims to engage in forgiveness, providing the necessary encouragement and understanding to navigate this challenging journey. The study underscores the importance of integrating religious guidance with psychological support, highlighting the significant psychological benefits of forgiveness for DV survivors, including improved emotional well-being and interpersonal relationships.